Analisis Makna Tanda pada Poster Film Perahu Kertas - Hasbullah Hasbullah; Risyaf Kudus Pranasa (Universitas Bumigora, 2023)
The Paper Boat film is an adaptation of the novel by Dewi Lestari with the youth romance genre which was first published in digital form (WAP) in April 2008, until finally it was successfully published in a book and published in 2009 by Bentang Pustaka. Paper Boat itself is Dee's sixth novel and his first novel with a popular genre. Departing from the background that the researcher described, the researcher is interested in analyzing and dismantling the visual meanings contained in the film poster